13th International Conference on Computational Intelligence in Security for Information Systems (CISIS 2020) - Herrero, Álvaro; Cambra, Carlos; Urda, Daniel; Sedano, Javier; Quintián, Héctor; Corchado, Emilio (Advances in Intelligent Systems and Computing, 2021)
XVII, 472 p. 177 illus., 128 illus. in color.